Arne Naess: A Tragic Ecosophy - Troiano, Ambra (ETHICS IN PROGRESS, 2019)
Arne Naess was one of the first philosopher who try to find out a way to resolve the ecological crisis through philosophy. By analysing some of the main point of Naess‘ philosophy, the essay shows that his main interest was to legitimize the ecological movement. Philosophy becomes a political instrument and assumes a tragical character, because it takes on an impossible project. For Naess philosophy should provide a new total view to change man‘s attitude to nature. This analysis could help us to find out some critical points of a philosophy that try to be useful in the ecological crisis.